Time out. Perspectives on liturgical temporality - Cilliers, JH (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
The understanding of the relationship between past, present and future is of the utmost importance for the liturgy. This article gives a brief theological exposition of the phenomenon of time, followed by some liturgical implications, namely liturgy as remembrance (anamnesis) of the past; liturgy as discernment (phronÄ“sis) of the present; and liturgy as anticipation of the coming (adventus) of the future. These features form the contours of a liturgy that is sensitive to its dimensions of temporality.